2015
DOI: 10.1534/g3.115.019513
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Additive, Dominance, and Imprinting Genetic Variance Using Genomic Data

Abstract: Traditionally, exploration of genetic variance in humans, plants, and livestock species has been limited mostly to the use of additive effects estimated using pedigree data. However, with the development of dense panels of single-nucleotide polymorphisms (SNPs), the exploration of genetic variation of complex traits is moving from quantifying the resemblance between family members to the dissection of genetic variation at individual loci. With SNPs, we were able to quantify the contribution of additive, domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
43
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 47 publications
13
43
3
2
Order By: Relevance
“…A large contribution of dominance effects to the total genetic variance in DG has been reported in a previous study, performed on a smaller number of records from the same populations (Lopes et al . ). In our previous study, however, a genotypic model instead of a breeding model (as used in the current study) was applied, and the influence of dominance effects on the prediction accuracy of phenotypes was not evaluated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A large contribution of dominance effects to the total genetic variance in DG has been reported in a previous study, performed on a smaller number of records from the same populations (Lopes et al . ). In our previous study, however, a genotypic model instead of a breeding model (as used in the current study) was applied, and the influence of dominance effects on the prediction accuracy of phenotypes was not evaluated.…”
Section: Discussionmentioning
confidence: 97%
“…However, in a previous study (Lopes et al . ), we estimated additive, dominance, and imprinting variance of the trait backfat and observed that the largest dominance variation was found in the Large White population, and the smallest in the Pietrain population. This is the opposite of the results for DG in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For average daily gain in Duroc pigs, Su et al [9] estimated a ratio of 15%, but their results were based on genotypic variance components and cannot be directly compared to genetic variance components [32]. For average daily weight gain in Yorkshire and Landrace pigs, Lopes et al [44] reported ratios of 13.8 and 28%, respectively by including genomic information. For Fleckvieh cattle, Ertl et al [12] calculated ratios that ranged from 3.4% for stature to 69% for protein yield by using a univariate SNP-BLUP model.…”
Section: Discussionmentioning
confidence: 99%
“…Heritability estimated from a genomebased model was slightly less than the pedigree-based estimates for most traits using the same data (Table 4). Reduced estimates of heritability from a genome-based model as opposed to a pedigree-based model have been previously observed (Lopes et al 2015). This phenomenon has been referred to as the "missing heritability problem" (Lee et al 2011).…”
Section: Prediction Of Genomic Breed Compositionmentioning
confidence: 95%